“Don’t judge, listen to their story”: A narrative study on an elementary school teacher’s experiences in supporting children with special attention needs - Gupi Rohman Nurmansyah; Effy Mulyasari; Ikmal Redzuan; Dinn Wahyudin (Universitas Sebelas Maret, 2025)
This study interpreted and navigated the experiences of a teacher providing an inclusive approach to children in elementary school who required special attention. The study was motivated by the increasing cases of mental health issues among elementary school-aged children, which adversely affect various aspects of their lives. The gap between teachers' knowledge related to children's psychological problems is an important substance that deserves to be explored, because research like this is still rarely carried out. This research did not judge the rightness or wrongness of a teacher’s actions but prioritized the value of care in this exploration. Through a narrative inquiry, the study explored how a elementary school teacher’s care and experience manifested in attending to children exhibiting psychological symptoms influencing their behavior at school. The findings focused on the interpretation of narratives constructed by the teacher. Behaviors perceived as ‘naughty,’ hyperactive, anxious, or attention-seeking were understood as accumulations of family background factors. Hence, what was needed was not judgment but the teacher’s ability to dedicate time to listen to the child’s story and provide an inclusive approach. Psychological competence was not the foremost concern; rather, it was the teacher’s willingness and high level of care, demonstrated through actions aimed at helping students reach their optimal performance in life. Due to the research limitations, the findings recommend long-term studies involving multiple participants from diverse backgrounds for further exploration.